The Level of IgG to Coronavirus Infection among the Medical Institution Employees - M. A. Yunusova; E. S. Lutsenko; N. N. Tsapkova; A. Yu. Brazhnikov; T. S. Saltykova; V. S. Yudina (Эпидемиология и вакцинопрофилактика)
Relevance. In a pandemic, studies on the duration of immunity in those who have recovered from COVID-19 and the formation of resistance to a new coronavirus infection are of particular importance.Target. To study the retention time of IgG in the blood serum of employees of a medical institution who recovered from a new coronavirus infection COVID-19.Materials and methods. The assessment of the timing of the formation of IgG was first carried out 3 weeks after the illness in employees of The National Medical Research Center for Otorhinolaryngology from April 2020 to December 2020. Further, the intervals for blood sampling to study the dynamics of antibodies to coronavirus infection were 3–4 weeks (9 blood samples for each ). Antibodies were examined by ELISA; immunological method for determining IgG (test system – "Vector Best", semi-quantitative analysis). Statistical processing of the study results was carried out using the SPSS-22 statistical software package and the OpenEpiver statistical calculator. 3.Results and discussion. The proportion of employees of a medical institution who recovered from COVID-19 was 39%, among them persons aged 36 to 55 years prevailed. It was found that class G immunoglobulins persist from seven months or more in 56.3% of those participating in the observation (the positivity coefficient is much higher than 1.2), in about 12.7% of those who had been ill, IgG in the blood serum persisted for about six months, in 11, 3% about three months. There were no statistically significant differences in the duration of immunity between men and women.Conclusion. A statistically significant direct relationship was found between age and the duration of immunity.